(untitled) (Fiep Bulletin - online, 2016)
Objective: Analyse the social representations of Chilean Physical Education students regarding the meaning of Physical Education. Methodology: A non-experimental design, crossed-section, of mixed characteristic was used. The sample consisted of 200 Chilean Physical Education students, who were selected under an intentional non-probabilistic criteria, from 12 different universities of this country. For data collection, the natural Valdés & Hernández y Valdés & Reyes (Valdés1998) semantic networks technique survey was applied, with the words "Physical Education" as a stimulus. The total of concepts (J value), frequency of occurrence (M value), 15 higher hierarchical predominance words (SAM), and percentage of the semantic distance between the different defining words (FMG) were analyzed. Results: The results show the defining words Health, Sport, Kinetics & Movement as having a greater semantic importance. Conclusion: It’s concluded that the social representations of these specialities are connected with health and welfare, associated with the movement and the study of human kinetics, denoting a pedagogical value through elements such as physical activity, recreation and sport.